THE EFFECT OF PROBLEM BASED LEARNING INTEGRATED WITH ANDROID-BASED MEDIA ON EXCRETION SYSTEM MATERIALS TOWARDS THINKING SKILLS AND MASTERY OF CONCEPT - Fawanys, Yulinar; Ibrahim, Muslimin (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2019)
Abstract Today’s students are required to have problem solving skills to meet 21st century education competencies. Problem Based Learning is a learning model that requires students to find and solve their problems so that students’ interest in learning is significant. The use of media in learning can attract the interest of students, one of which is Android-based media so that research is conducted to analyze the effect of Problem Based Learning integrated with Android-based media on excretory system material on thinking skills and mastery of concepts. This research is a type of quasi-experimental research using matching-only pretest-posttest control group design. Sampling of research classes using purposive sampling technique, so that two classes were obtained as treatment and comparison classes. Student learning outcomes in the form of thinking skills and mastery of concepts were analyzed using SOLO taxonomy and carried out t-test. The results of this study indicate that the level of thinking skills and mastery of students’ concepts in the application of Problem Based Learning is integrated with Android-based media higher than students in the application of Problem Based Learning without integration with relational and extended abstract thinking skills and mastery of concepts as much as 80%. It can be concluded that Problem Based Learning integrated with Android-based media on excretory system materials influences thinking skills and mastery of concepts. Keywords: problem based learning, android media, thinking skills, mastery of concepts